GARLIC (Allium Sativum) EXTRACT EFFECTIVENESS TEST AGAINST TRICHOPHYTON RUBRUM AND PITYROSPORUM OVALE MUSHROOM - Yohana Christiani Marpaung; Adeline Adeline; Andre Budi; Grace Alvonsine (Universitas Negeri Gorontalo, 2022)
Seborrheic dermatitis and dandruff are chronic papulo squama skin disorders. with a predilection for areas rich in sebum glands, scalp, face and body. Tinea corporis itself is a dermatophytosis in area of the body skin that has no hair (glabrous skin). In general, itchy rashes are found on the body, extremities or face. Methods: this type of research is experirnental then the research design uses the disc diffusion method with the Posttest Only Control Group Design. Each treatment for 1 mushroom was repeated 4 times, thus the total sample for 2 mushrooms was 16 samples. The extract concentration was made into 4 concentration, namely 15%, 30%, 45%, 60% and positive control (ketokenazole) then the inhibition test was carried out on both fungi, namely Trychophyton rubrum and Pityrosporum ovale using PDA (Potato Dextrose Agar) media. Results: The research showed that garlic ethanol extract could inhibit fungal growth at concentrations of 15%, 30%, 45%, 60% and positive control (ketokenazole) with an average diameter of the inhibitory zone power test for Trychophyton rubrum 6.85mm, 7.00mm. , 7.50mm, 8.35mm, and 12.30mm. And for the power test the inhibition zones of Pityrosporum ovale were 6.50mm, 11.50mm,12.40mm,15.00mm, and 20.50mm. Conclusion: The conclusion of this study shows that garlic extract has the power to slow down the growth of the fungi Trychophyton rubrum and Pityrosporum ovale in concentrate 60% is 15,00mm and 8,35mm.